Persistence Detection of Sars-Cov-2 RNA in Healthcare Workers with COVID-19: A Case Report - Jum Ahmad, Ilzy; Mulyo, Sostro; Ikram Hasanuddin, Abdi Dzul (Green Medical Journal, 2020)
Coronavirus Disease 2019 (Covid-19) has now become a concern around the world. Until 6 September 2020, there were 190,665 cases in Indonesia, and it was in the third rank of most cases in the Asian region. It is important to determine the criteria of return to work for healthcare workers with Covid-19 positive in Indonesia. This case report discussed a female patient, 32 years old with chief complaint of fever and itchy throat since 2 days ago. She is a health care worker in the hospital, with a history of treating patients with positive confirmation of Covid-19 for 2 days in the ordinary ward before the case was confirmed with a history of contact approximately 5 days ago. The patient was diagnosed with positive confirmation of Covid-19 and was required for self-isolation. The patient still had positive results of RT-PCR Covid-19 up to the third examination in 30 days after the initial RT-PCR testing, although received specific antiviral treatment with oral oseltamivir and oral supplementation. Based on growing evidence that Sars-Cov-2 may not infectious for more than ten days in the mild-moderate disease, this case report is strengthening the use of symptom-based strategic approach to determine when to return to work in Indonesian healthcare workers with positive COVID-19.